Kalinangan 1996 [held at] Osaka University of Foreign Studies, Department of Philippine Studies on November 4, 1996 ([Osaka s.n., 1996)
Cultural presentation of students at the Department of Philippine Studies Department in Osaka, featuring Philippine dances and songs and a skit about the Philippine flag.
Keywords: Philippines -- Culture; Philippines -- Relations -- Japan